Studies in Hispanic and Lusophone Linguistics (De Gruyter Mouton, 2008)
This journal deals primarily with the linguistic analysis of Hispanic and/or Lusophone languages, which is interpreted broadly so as to include not only Spanish and Portuguese, but also Catalan, Galician, Spanish- and Portuguese-based creoles, and other such areas of investigation. Beside research articles, the journal also features book reviews, and articles on the current status and recent developments of work in specific subareas.